Study on the induction of exogenous plant hormones to enhance the weed suppression ability of allelopathic and non-allelopathic rice accessions - Ting Wang; Xinyi Ye; Yuhui Fan; Shuyu Chen; Huayan Ma; Jiayu Li (PeerJ, 2025)
Background Increasing the induced-allelopathic potential of rice at the seedling stage by chemical induction is an important strategy in weed management. More in-depth work is needed to find inducing agents for effectively improving the weed-suppressive activity of allelopathic and non-allelopathic rice accessions via the modulation of root morphology and allelochemicals production. Methods Grown in Hoagland’s solution, two rice cultivars—allelopathic PI312777 (PI) and non-allelopathic Lemont (LE)—were treated using various phytohormones to evaluate root growth and allelopathic potential. Optimal phytohormones (ABA and EBL) were selected based on root growth responses. Extraction of rice leaf and root exudates, subsequently assessed on lettuce seedlings, revealed induced allelopathy. WinRHIZO software was used to investigate root morphologies; HPLC and GC-MS evaluated phenolic acids and terpenoids in rice tissues. The transcription of genes related to phenolic acid and terpenoid biosynthesis was measured by qPCR. ANOVA and correlation analysis were applied in data analysis. Results The results showed that the optimal induction conditions were abscisic acid (ABA, three µmol/L) or 24-epibrassinolide (EBL, 0.5 nmol/L) for 3 days. Under these conditions, the induced-allelopathy (IA) values of rice root exudates induced by three µmol/L ABA were 9.62% in PI31277, and 13.76% in Lemont, while the IA values of PI31277 and Lemont after 0.5 nmol/L EBL treatment were 7.83% and 11.51%, respectively. ABA mainly affected the root length and volume at 0–0.2 mm diameter, while EBL mostly affected root length and volume at 0–1.0 mm diameter. The total content of phenolic acids in root-exudates of PI31277 and Lemont induced by EBL were 1.16 and 2.33 times greater, respectively, while ABA induction also increased the phenolic acid content by 1.48 and 1.87 times, respectively. Most genes related to phenolic acid and terpenoid synthesis, such as PAL, C4H, F5H, MK, SQS, and PS, were upregulated after EBL induction, while most genes were downregulated after ABA treatment. Moreover, correlation analysis confirmed that root morphology, allelochemicals production, and related gene expression levels were significantly correlated with induced-allelopathy caused by ABA or EBL treatment.